ONETEP: linear-scaling density-functional theory with plane-waves - Mostofi,AA; Haynes,PD; Skylaris,CK; Payne,MC (2007)
Conventional methods for atomistic simulations based on density-functional theory (DFT), such as the plane-wave (PW) pseudopotential approach, have had an immense impact on the way in which material properties are studied. In spite of this success, the system-size accessible to such techniques is limited because the algorithms scale with the cube of the number of atoms. The quest to bring to bear the predictive power of DFT calculations on ever larger systems has resulted in much recent interest in linear-scaling methods for DFT simulations. To this end we present an overview of ONETEP (Order-N Total Energy Package), our linear-scaling method based on a PW basis set, which is able to achieve the same accuracy and convergence rate as the conventional PW DFT approach. The novel features of our method which result in its success are described and results of calculations on titanium oxide clusters from the ONETEP parallel code are presented.